The Effect of Gibberelin in Salin Soil on Growth of Vetiver (Vetiveria zizanioides L.) - Novita, Aisar; Rahmawati, Nini; Cemda, Abdul Rahman; Nora, Silvia; Harahap, Fitra Syawal (Jurnal Online Pertanian Tropik, 2021)
Salinity is one of the problems in agricultural land in the world, including in Indonesia. Vetiver is quite tolerant of planting in saline soils at a certain level of salinity, but vetiver growth is inhibited at high salinity levels. The purpose of this study was to evaluate the effect of gibberellin in saline soils on the growth and production of vetiver (Vetiveria Zizanioides L.). This research was conducted in the greenhouse of the Faculty of Agriculture, Universitas Sumatra Utara, Medan. This study used a non-factorial completely randomized design, It was salinity stress (S) which consisted of 3 factors: Gibberellin concentrations of 0 (without treatment), 50 ppm, and 100 ppm. The results of this study indicate that giving Gibberellins in salinity stress conditions has a significant effect on the observed variables of plant height, specific leaf area, and cuticle thickness.